2021
DOI: 10.1007/s11528-021-00589-6
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Educational Technology: What Facebook, Twitter, and Scopus Can Tell us about Current Research and Practice

Abstract: Using large-scale, public data sources, this editorial provides a high-level description of educational technology trends leading up to and encompassing the year 2020. Data sources included (a) 17.9 million Facebook page posts by K-12 educational institutions in the U.S., (b) 131,760 tweets to the #EdTech hashtag on Twitter, and (c) 29,636 educational technology articles in the Scopus database. We provide a variety of descriptive results in the form of participation frequency charts, keyword matches, URL domai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 21 publications
1
30
0
1
Order By: Relevance
“…One study used posts on Facebook to understand what educational technologies K-12 educational institutions used. In this study, the authors examined the links included in millions of posts by United States schools and districts, finding that Google-owned domains associated with tools for finding, sharing, and managing myriad files were the most predominant (Kimmons et al, 2021). This study on the sharing of links is one example of the kind of research on topics and events and people and organizations that have been the locus of much of the research using data from Twitter.…”
Section: Studying the Educational Uses Of Facebook Using Traditional And Newer Methodsmentioning
confidence: 99%
“…One study used posts on Facebook to understand what educational technologies K-12 educational institutions used. In this study, the authors examined the links included in millions of posts by United States schools and districts, finding that Google-owned domains associated with tools for finding, sharing, and managing myriad files were the most predominant (Kimmons et al, 2021). This study on the sharing of links is one example of the kind of research on topics and events and people and organizations that have been the locus of much of the research using data from Twitter.…”
Section: Studying the Educational Uses Of Facebook Using Traditional And Newer Methodsmentioning
confidence: 99%
“…(Mishra et al, 2021). In 2020, trends in educational technology showed the use of social media, Facebook, Twitter in online learning (Kimmons et al, 2021). During the COVID-19 pandemic, there has been an explosion in the use of educational technology, which has shifted traditional learning to learning that applies information technology (Nguyen & Chung, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…As the number of people using social media has increased, the risks to the privacy of social media users have also increased [23], and this is particularly true since social media use expands into areas of our lives that it did not previously occupy. Education is one such domain in which social media use is now widespread [2,10,11,13,21,22]-and is one domain for which the privacy risks from social media use, in general, may be compounded because of the centrality of a particularly vulnerable population, minors at school.…”
Section: Introduction and Prior Researchmentioning
confidence: 99%
“…While past research has explored the willingness of social media participants and students to share their data for research, a different-institutional rather than personal-context for social media use presents potentially notable privacy risks. Namely, past research has shown that both post-secondary [13] and K-12 educational institutions use social media extensively; particularly, Twitter and Facebook [10,11]. However, to this point, no research has yet investigated privacy in the context of social media use by K-12 educational institutions.…”
Section: Introduction and Prior Researchmentioning
confidence: 99%
See 1 more Smart Citation